Guest Decision To Book A Hotel Room Through Social Media : The Mediation Effect Of Behavioural Intention - Muhammad Alfarisyi; Feri Ferdian (Gemawisata: Jurnal Ilmiah Pariwisata, 2023)
The influence of social media on guest decision behavior in booking hotel rooms is increasingly relevant in today's digital era. Social media provides a broad platform for guests to seek information, interact, and make decisions regarding hotel room bookings. Perceived ease of use is an important factor influencing guests' decisions, where an intuitive interface, simple navigation, and a smooth booking process will influence their conclusion to make a booking through social media. In addition, perceived helpfulness is also a key consideration, where relevant information, reviews from previous guests, and useful recommendations on social media can shape positive perceptions and encourage guests to take the next step. Booking intention, as a result of perceived ease of use and usefulness, is also an important variable that influences guest behavior. This research aims to study and identify guests' decisions in booking hotel rooms through social media. One of them is to find out whether social media as a channel for booking hotel rooms is useful, easy to use, and easily accessible to the wider community. the type of research used is a quantitative approach with an explanation (explanatory research). The variables in this study are perceived easy use, perceived usefull, booking intention, and decision to book a hotel room. the population used in this study were UNP Hotel & Convention Center guests. The number of samples used was 111 respondents with purposive sampling technique and describe data from respondents' answers to questionnaires along with inferential statistical analysis techniques using the SEM (structural equilibrium modeling) data analysis method with the PLS (partial least square) approach. SmartPLS 3.intention order application. Booking intention significantly mediates between perceived ease of use and the decision to book a hotel room on social media. Social media. This is because the coefficients from X to M and M to Y are significant in both.